Functional analysis of a novel variant in the COL5A1 gene in a Polish patient with the classical type of Ehlers–Danlos syndrome - Junkiert-Czarnecka, Anna; Maciak, Karolina; Kacprzak, Magdalena M.; Łobodzińska, Agnieszka; Sobczyńska-Tomaszewska, Agnieszka; Jurkiewicz, Aneta; Gora, Monika; Burzynska, Beata; Pilarska-Deltow, Maria; Haus, Olga (Frontiers in Genetics, 2025)
Ehlers–Danlos syndrome (EDS) is a clinically and genetically diverse group of inherited connective tissue disorders. According to the 2017 International Classification, 13 EDS subtypes are associated with pathogenic variants in 19 genes, most of which are involved in collagen synthesis or structure. The most common forms include classical (cEDS) and hypermobile (hEDS) types. Classical EDS is primarily caused by pathogenic variants in the COL5A1 and COL5A2 genes, which encode type V collagen, and less frequently by the c.934C>T variant in COL1A1. This study investigated the molecular basis of cEDS in a 9-year-old girl presenting clinical features consistent with this subtype. Whole-exome sequencing (WES) identified a novel variant in COL5A1: c.2089-7_2089dupGTACACAG. Functional analysis showed that this duplication causes a shift in the exon start site, resulting in a premature stop codon and a predicted truncated protein lacking approximately 1,000 amino acids. Family studies confirmed that the variant occurred de novo. This pathogenic variant, located in the triple helical domain of type V collagen, likely disrupts the final structure and function of the protein. The two-step diagnostic strategy combining molecular and functional testing enabled a rapid and definitive diagnosis for the patient.